INTEGRASI CRM BERBASIS TEKNOLOGI DAN KEBERLANJUTAN : MODEL HOLISTIK UNTUK MENINGKATKAN LOYALITAS PELANGGAN DI ERA DIGITAL - Nurdiana Nurdiana; Rahmawati Umar; Khaddafy Thayyeb (LPPM STIE Muhammadiah Bandung, 2026)
ABSTRACT This study aims to explore the implementation of Customer Relationship Management (CRM) based on digital technology and sustainability in enhancing customer loyalty. The digital technologies referred to include cloud-based systems, artificial intelligence (AI), and data analytics that enable companies to better understand and personalize customer experiences. Furthermore, the study also emphasizes the importance of integrating sustainability into CRM, such as environmentally friendly products and Corporate Social Responsibility (CSR) programs, in strengthening customer loyalty. The research method used is a literature review, analyzing articles from journals, books, and industry reports published in the last ten years. The results indicate that digital technology, especially through AI and data analytics, improves companies' ability to personalize services, which in turn strengthens customer loyalty. Additionally, sustainability in CRM, both through eco-friendly products and involvement in CSR programs, plays a crucial role in enhancing the emotional connection between customers and brands. This research concludes that the integration of digital technology and sustainability in CRM provides companies with a competitive advantage in building long-term relationships with more loyal and engaged customers. Therefore, companies need to adopt the right technologies and consider social and environmental values to strengthen their customer loyalty. Keywords :Customer Relationship Management (CRM), Digital Technology, Personalization, Sustainability, Customer Loyalty